Grain Amaranth as an Alternative and Perspective Crop in Temperate Climate - Grobelnik Mlakar , Silva; Turinek, Matjaž; Jakop, Manfred; Bavec, Martina; Bavec, Franc (Journal for Geography, 2010)
As a consequence of globalisation and industrialisation of agriculture, global food security has become increasingly dependent on only a handful of fertilisation and energy high demanding plant species. This involution has increased the vulnerability of agriculture, reduced genetic diversity, provoked some environmental problems and impoverished the human diet. The mentioned facts stimulate the retrieving of alternative crops into the production. The present paper briefly describes crop importance, botany, nutritional value and utilisation of grain amaranth (Amaranthus spp.), one of the alternative crops discussed in the book Organic Production and Use of Alternative Crops. The immediate objective of this paper is to present information gained as a result of a national project on grain amaranth.